Factors Affecting Cold Chain Logistics Performance with Supply Chain Resilience as a Mediating Variable - Zaky Assiddiqie; Triwulandari Satitidjati Dewayana; Wahyuningsih Santosa (Eduvest - Journal of Universal Studies, 2026)
This research aims to analyze the influence of demand, quality, technology, and cold chain logistics risks on supply chain resilience and its impact on cold chain logistics performance, including the role of supply chain resilience as a mediating variable. The study employs a quantitative approach using a survey method targeting stakeholders in the cold chain logistics industry, with data analyzed through Structural Equation Modeling (SEM). The results show that demand, quality, and technology have a positive effect on supply chain resilience, whereas cold chain logistics risks have no significant effect. Supply chain resilience is proven to have a positive and significant effect on cold chain logistics performance and mediates the influence of demand, quality, and technology on performance, while mediation through the risk variable is not supported. Additionally, technology and cold chain logistics risks have a direct effect on cold chain logistics performance. These findings confirm that improving cold chain logistics performance is more effectively achieved by strengthening supply chain resilience through robust demand management, consistent quality systems, and the application of technology. This conclusion can serve as a basis for managerial decision-making and cold chain logistics policy development..